(untitled) - Pezeu-Massabuau, Jacques (Rutland, Vt., 1978)
1. One hundred million people on twenty million acres ; 2. An inhospitable environment;...
Keywords: Japan,Nhật Bản; Social conditions,Điều kiện xã hội; 1945-1989,1945-1989